Fitoplancton del Golfo de Cariaco, estado Sucre, Venezuela - La Barbera-Sánchez, Amelia (1999)
Phytoplankton was sampled monthly during the lune 1995-May 1996 period, at 16 stations of the eastern Gulf of Cariaco. This area receives different wastes. Only chlorophyll and diatoms, dinoflagellates, and total density of phytoplankton varied by depth. Only salinity and oxygen showed horizontal spatial differcl1tiation. Phytoplunkton maxima in November- December, were related with low nitrogenous nutrients and temperature, high phosphate, chlorophyll, and dissolved oxygen. The June-October period was characterized by high temperature, low oxygen, nutrient concentrations and phytoplankton abundance. Overall, phytoplankton abundances were low. Diatoms dominated during the sampling period, but microflagellates and dinoflagelates did occasionally. Phytoplankton density was positively correlated with phosphate and negatively with nitrogen. In spite of the high nutrient supply, phytoplankton growth was limited by a reduced light penetration related to concentrations of suspended particles.